The Blackwell Companion to the Hebrew Bible - Phillips, Anthony (Journal of Semitic studies, 2004)
The Blackwell Companion to the Hebrew Bible Leo G.Perdue , (Blackwell Companions to Religion 3). Blackwell Publishing, Oxford 2001. xxx + 471. Price: £80.00 . ISBN: 0-631-21071-7